Pilot‐scale production and physicochemical characterisation of spray‐dried nanoparticulated whey protein powders. (10th June 2021) - Guralnick, Jacob R; Panthi, Ram R; Bot, Francesca; Cenini, Valeria L; O'Hagan, Barry MG; Crowley, Shane V; O'Mahony, James A
Abstract : Spray‐dried whey protein isolate (WPI) powders were prepared at pilot‐scale from solutions without heat (WPIUH ), heated (WPIH ) or heated with calcium (WPIHCa ), which were analysed and compared with a control sample (WPIC ). WPIC, WPIUH, WPIH and WPIHCa solutions had whey protein denaturation levels of 0.0, 3.2, 64.4 and 74.4%, respectively. Computerised tomography scanning showed that 52.6, 84.0, 74.5 and 41.9% of WPIC, WPIUH, WPIH and WPIHCa powder particles had diameters of ≤30 µm. WPIHCa and WPIH powders were cohesive, while WPIC and WPIUH powders were easy flowing. Marked differences in microstructure were observed between WPIH and WPIHCa . There were no measured differences in wall friction, bulk density or colour. Abstract : Production and physicochemical characterisation of whey protein isolate powders containing nanoparticulated whey proteins.